PERSEPSI KONSUMEN TERHADAP MAKANAN ORGANIK DAN PEMBENTUKAN STRATEGI BUSINESS CANVAS PADA START UP ORGANIC MARKET DI KOTA SURABAYA - Zainal Arifin; Nimas Aryany Pratiwi; Bondan Dewa Brata (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to analyze consumer preferences for organic food in Surabaya and recommend the strategic implications of using the Business Model Canvas to open organic food outlets. The research design was carried out with a quantitative descriptive method approach. The sampling method was carried out by judgmental sampling technique, with the respondents' criteria being 100 consumers of organic products. In this study, the types of data collected were: primary data in the form of a questionnaire distributed to people who shop at organic food restaurants in Surabaya; secondary data, as the data or information obtained through literature studies, theories, and literature related to organic food, and the variables used are perceptions of lifestyle, perceptions of health, perceptions of environmental impacts and perceptions of the Greens community as independent variables and interest in buying organic products in Surabaya as the dependent variable. This research provides strategic implications of managerial strategies in the activity of organic food outlets to increase sales using a marketing strategy consisting of production, price, promotion, distribution and this strategy is helpful in linking consumers in terms of quantity, quality, and balance that can provide better profits.